A Marking System for Scintillation Camera and Computer, and Its Clinical Application - ITO, Kazuo; KAHATA, Shun; YAMAGUCHI, Hiroshi; NARABAYASHI, Isamu; YOSHIDA, Shoji (RADIOISOTOPES, 1976)
In routine clinical studies, we have experienced some cases of transferring anatomical marks to scintigrams through the scintillation camera. It was thought that radioactive point sources could be used as anatomical marks.However, this method resulted in an ill-defined area of brightness. A marking equipment for scintillation camera used in this study consists of linear potentiometer and sine-cosine potentiometer. Moreover we designed a marking method for a data processing system using the marking equipment for scintillation camera. A data processing system of scintillation camera is composed of EDR-4000 (8K core memories), MT recorder, CRT display, graphic display unit, and is connected by on-line with scintillation camera. A marking program was made in order to record marking addresses on a processed image. Using this soft program and graphpen of graphic display unit, we transferred marks to processed image by points and lines. The subtraction scintigraphy using 198Au-colloid and 75Se-selenomethionine was performed on cases of pancreas carcinoma. After marking addresses were recorded on a processed image by this marking method, the signals from the scintillation camera were fed into input controller. Then these signals with marking points were transferred from computer to MT recorder. The subtraction scintigraphy by this system made it possible to examine each picture with 198Au-colloid or 75Se-selenomethionine at different times.